Legal Aspects in Implementing an Informed Consent System in Patient Health Practices - Irsyam Risdawati (International Journal of Society and Law, 2024)
This research explores the legal aspects related to the implementation of the Informed Consent System in patient health practice. This system is a crucial ethical foundation in the relationship between medical personnel and patients, ensuring thorough understanding before patients consent to medical procedures or research. The research focus includes analysis of legal requirements, authority rights, and legal consequences related to Informed Consent. Additionally, this research investigates recent developments in health law, such as data protection and patient privacy regulations, and explores legal cases that can shape the framework for practice. By detailing the legal aspects involved, this research aims to provide a holistic view of the implementation of the Informed Consent System, strengthen regulatory compliance, and encourage a better understanding of rights and responsibilities in healthcare practice. It is hoped that the implications of this research will provide solid guidance for health practitioners and researchers in ensuring legal and ethical compliance in administering Informed Consent.